In vitro effects of famotidine and ranitidine on lower esophageal sphincter tone in rats - Mahmut ÖZER; Mustafa DUMAN; Şükrü TAŞ; Yeliz DEMİRCİ and Muhammet Fatih AYDIN and Enver REYHAN and Ali Emre ATICI and Erdal Birol Bostancı and Musa AKOĞLU and Ece GENÇ (Turkish Journal of Gastroenterology, 2019)
-